Beyond the passbook relationship: Assessing preferences for contracts among cotton and tea farmers and companies in Malawi - Ochieng, Dennis O. (International Food Policy Research Institute, 2020)
While contract farming provides opportunities to link smallholder farmers to markets, its sustainability depends on how the interests of both farmers and buyers are addressed. Previous studies analyze farmers’ preferences for contracts, but buyers’ preferences for contracts and design attributes are hardly examined. This Working Paper contributes to the knowledge gap by analyzing farmers’ and buyers’ preferences for contracts and design attributes, and the similarities and differences in preferences using a discrete choice experiment with 505 cotton farmers and 512 tea farmers in southern Malawi. Using a mixed logit model, the author examines farmers’ and buyers’ preferences and estimate farmers’ willingness to pay for improvement of contract attributes. Results show that both farmers and buyers have positive preferences for contracts in general and for many design attributes. The author however observes clear differences in preference for payment mode where farmers prefer spot payments while buyers prefer delayed payments. Further, while both parties prefer better quality products, there are no standardized grading systems for the two crops in Malawi. Consequently, buyers are skeptical of farmers’ ability to produce quality products while farmers are distrustful of buyers’ grading systems. Even though buyers are open to offer contracts that provide inputs or insurance to farmers, there are no information sharing platforms to guide in contracting farmers thus exposing buyers to risks of contract default. The author also finds that farmers prefer contracts that address their social needs as seen in their choice of contracts with funeral expenses insurance. Such attributes could strengthen the relationship between farmers and buying companies. Sustainable contract schemes require designing contracts that are acceptable to both farmers and buyers by balancing risks between the parties. Successful contract relationships have to build business relationships and foster mutual trust by developing standardized grading systems and information sharing platforms for buyers and farmers to guide selection into the schemes. To minimize side-selling, companies can advance cash credit to liquidity constrained farmers, but this must be accompanied by stronger contract enforcement mechanisms.